San Miguel Foods, Inc. - feeds business - Hilotina, Francis E.; Digal, Larry N.; Concepcion, Sylvia B.; Gomez, Aurelia Luzviminda V. (Davao City School of Management, University of the Philippines Mindanao, 2008)
Today, the increasing difficulty of growing an agribusiness, let alone surviving one, does not spare the feed business of SMFI. Contributing factors and evolving trends are not uncommon: (1) Dramatic increase in the environment?s complexity. (2) Increasing difficulty of predicting the future with accuracy. (3) Increase number of variables. (4) Rapid rate of obsolescence of even the best plans. (5) Increase in the number of both domestic and world events affecting organizations. (6) Decreasing time span for which planning can be done with any degree of certainty [David, 3rd edition, p.319]. This paper will evaluate present difficulties underpinning SMFI?s corporate objectives. It aims to determine how SMFI aligns its Feed Business with the current corporate strategies hinged on the combination of an expanded product range, broadened distribution, and increased efficiencies. A further review made on how SMFI grows its operations with the entire SMPFC business platform, achieves a more efficient business model, and builds on a stronger manufacturing base growth, innovation and continued success. This study adopts the strategic management framework of Fred David and implementation model of balanced scorecard by Robert Kaplan and David Norton. It directs a comprehensive evaluation of the strategic planning fundamentals applies by the company to determine if its operating resources are efficiently managed to deliver its business objectives, both in immediate and future timeframe. For a company that has grown to lead an industry amidst unique economic challenges this study will be an inward-looking assessment of the company?s ability to effectively respond and adapt to changing domestic and global markets. Company strategies take pride of he positive outcome of implemented strategies. Successive ?better-than-average? industry performance is demonstrated by so far realized annual business goals. However, in the fast-changing world today, the time to celebrate success is too short. Complacency and over-indulgence in past performance offer no guarantee for continue success. Building on its present strength makes the company resilient, but responsive strategic planning allows its resources to tame evolving trends and complexities, pursue and attain better goals. There are, however, limits to the degree of information disclosure permissible owing to the delicate nature that may expose the company?s vulnerability to competitor action. Although sensitive data are deliberately disguised to afford such protection, nonetheless, the analyses processed in this paper are by themselves opening a welcome view of the company?s strategic insights.
Thesis, Graduate (Master in Management)--University of the Philippines Mindanao, December 2008